Estrés térmico al que está expuesto el personal de operaciones de la Planta de Gas del Complejo Industrial Shushufindi (CIS) y su afectación a la salud, propuesta de un programa de prevención, 2016. - Garrido Mejía, Ismael Antonio (2018)
This work research consist of a risky study about the thermal stress which is exposed the operation staff at the CIS gas plant and its health effects, to develop a proposal of a prevention program. It was implemented the WBGT index method according to the NTP 322 technical norm because of its simplicity and easy application. Through this method, it was established the risk existence; therefore, the gas plant was divided into four zones. In this labor environment, there are 12 operators who work daily as supervisors, leaders technicians and technicians’ operators. With the purpose that the study has a transversal characteristic, the operation staff at the gas plant and the Occupational Doctor were interviewed in order to propose controls and in this way it can be prevented illnesses related to the thermal stress. The proposal of a prevention program determined the control actions to the established aspects as high risk. They are referred to the general controls, and controls to the workers, using preventive actions which are recommended in the Ecuadorian law.